1999
DOI: 10.1200/jco.1999.17.9.2876
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Plus Cisplatin, an Active Regimen in Advanced Urothelial Cancer: A Phase II Trial of the National Cancer Institute of Canada Clinical Trials Group

Abstract: Gemcitabine plus cisplatin is an active regimen for the treatment of urothelial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
64
0
9

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(83 citation statements)
references
References 11 publications
10
64
0
9
Order By: Relevance
“…Kaufman et al (19), reported an overall response rate of 41% (CR: 22%, PR: 19%), a median time to treatment failure of 5.5 months and a median overall survival of 14.3 months for the metastatic urothelial cancer patients who were treated with GC. Moore et al (20), reported that using GC for advanced urothelial cancer produced an overall response rate and a median survival of 57% (CR: 21%, PR: 36%) and 13.2 months, respectively, which concurs with our findings of an overall response rate and a median survival of 36% (CR: 24%, PR: 12%) and 20 months, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Kaufman et al (19), reported an overall response rate of 41% (CR: 22%, PR: 19%), a median time to treatment failure of 5.5 months and a median overall survival of 14.3 months for the metastatic urothelial cancer patients who were treated with GC. Moore et al (20), reported that using GC for advanced urothelial cancer produced an overall response rate and a median survival of 57% (CR: 21%, PR: 36%) and 13.2 months, respectively, which concurs with our findings of an overall response rate and a median survival of 36% (CR: 24%, PR: 12%) and 20 months, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…However, in our study, the progression free and overall survival of patients with good PS, despite age and impaired renal function, were 6.4 months and 16.4 months, respectively, and compared favorably with the survival reported in patients on cisplatin-based trials. 4,14,18 Recently Vaughn and et al 30 reported a 50% objective response rate with carboplatin plus paclitaxel in patients with advanced age and reduced renal function; however, this combination was not devoid of significant toxicities: 15% of patients experienced Grade 3 peripheral neuropathy, Grade 3-4 neutropenia was observed in 39% of cycles, and 21% of patients experienced at least of one episode of febrile neutropenia. G-CSF was required in 26% of cycles.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 New agents, including gemcitabine, [7][8][9][10] paclitaxel, 11 and docetaxel, 12 have shown activity in patients with bladder and urinary tract transitional cell carcinomas. In Phase II trials, gemcitabine has been combined successfully with cisplatin, [13][14][15] paclitaxel, 16 and paclitaxel plus carboplatin, 17 producing interesting response rates and median survivals. A recently published multicenter, randomized study comparing M-VAC with gemcitabine plus cisplatin (GC) documented no differences in activity, progression free survival, and overall survival, with a tolerability profile favoring GC.…”
mentioning
confidence: 99%
“…The objective has been to find combinations that demonstrate improved efficacy and a better toxicity profile compared with that of M-VAC. The most extensively studied drugs have been gemcitabine (Moore et al, 1999;Von der Maase et al, 1999;Kaufman et al, 2000) and paclitaxel (Redman et al, 1998;Vaughn et al, 1998;Zielinski et al, 1998;Dreicer et al, 2000;Small et al, 2000), each in combination with cisplatin or carboplatin. These studies have usually shown an elevated activity with a favourable toxicity profile (Table 3).…”
Section: Discussionmentioning
confidence: 99%